Study of Progress Difference on Building Construction Works - Mardiaman Mardiaman; Daud Surbakti (Green Publisher Indonesia, 2022)
The progress of construction work has different deviations at a certain point in time. Various factors cause inequality. A positive progress deviation indicates that construction work is completed faster where the progress of the plan is lower than the actual one, otherwise it is said to be late if it is negative. The uncertain nature of construction work causes there are 3 (three) scenarios of possible progress deviation values, so that these three values ​​form one expected progress deviation value. A deviation of value greater than negative 10% for a duration from 0 to 70% is categorized as a critical contract. The purpose of this study was to determine the deviation of the progress of 29 construction works. Data collection was carried out on 29 construction works that had been carried out. The data is taken directly from the contractor. The results of data analysis showed that at 10% D, 11 construction works with poor performance were obtained. Information was also obtained that the construction work No. 12 have critical contracts (-11,773). Furthermore for the current construction work 30%D. 50% D and 70% D number of poorly performing construction works 12; 10; and 9. The value of the largest positive progress deviation is 15,362 at the 70% time point D. The expected value of the largest positive progress deviation is positive 1.763. By knowing the expected negative progress value, the contractor must exercise control as soon as possible before the contract expires. Acceleration can be done on activities that are on the critical path